On Calculation of Breakdown Electromagnetic Field in Low-Temperature Microwave Plasmatron - Tsarin, Yu. A. (Видавничий дім «Академперіодика», 2013)
On Calculation of Breakdown Electromagnetic Field in Low-Temperature Microwave Plasmatron